In-Vivo Animal Models For Screening Of Anti-Diabetic Activity - V.VARUN RAJ; L.SRIKANTH; L.VENKATESHWARLU (International Journal of Pharma and Bio Sciences, 2010)
This review summarizes the use of different animal models of Type 1 and Type 2 diabetes for screening the antidiabetic activity. A detailed review on surgical and non surgical methods, Genetic models of diabetes, various animal strains that spontaneously develop diabetes, the limitations of the different animal models and the different chemicals that are used to induce Diabetes mellitus has been discussed. The species of animal used is determined by several factors. In general, the smaller the animal, the more manageable and cheaper the experiment. Hence, pancreatectomised rats and mice are the most commonly used. Special attention has been paid to the animal models of Type 1 and Type 2 diabetes. The purpose of this review article is to describe the significance of various animal models available for screening of antidiabetic activity.